If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + 4x) = 0 (1 * -7 + 4x * -7) = 0 (-7 + -28x) = 0 Solving -7 + -28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -28x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -28x = 0 + 7 -28x = 0 + 7 Combine like terms: 0 + 7 = 7 -28x = 7 Divide each side by '-28'. x = -0.25 Simplifying x = -0.25
| 16z-32+9=2z+86 | | 8(5-4x)= | | 37803/x=0.75 | | 149388/x=0.73 | | xsqure+9=0findx | | -2m+9-4m-13= | | 6x-15-4x-(-8)= | | -14b+7y-5b-10y= | | -11g+8h-3g-7h= | | -7w-6k+4w= | | -8m+3+10+3m= | | 9917/X=0.74 | | (x+30)(x-3)=40 | | 68=-16t^2+80t+4 | | 32/X=0.32 | | 3x+4y-z=1 | | 5(3-2x)+25=4x-6(10-3x) | | 2n^3-2n=0 | | A+b=2015 | | 9x^2+4x-544=0 | | 3x^2-10x=15-2x^2 | | 4n+12=16 | | x-56=-220 | | -56=-220 | | 1.50*14= | | bx^8+2*a^4+c=0 | | x^8+2*x^4+3=0 | | 5h(3h-2)= | | 3/8%25= | | 2x(3x-6)(6x+3)=0 | | 8(4)+4y=6 | | V+f=e+2 |